Ketentuan Pendirian Perseroan Terbatas Setelah Berlakunya Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Anak Agung Ayu Intan Puspadewi (Jurnal Analisis Hukum, 2022)
Limited liability is a legal entity that most all businessmen are interested in because it is toward open business opportunities. Limited liability is a legal entity consisting of a capital and stock fellowship. After the passage of the limited liability company Work Copy Act not only a legal body consisting of capital and stock communion but a liability law body with micro and small business criteria. The problem of this research law issue is that it is concerned with the limited liability company criteria specified in the Working Copy Act and the establishment of limited liability companies that meet the criteria of micro and small businesses. The study used normative research methods with a statutory approach, analysis approach and concept approach. Tehnik collection of legal materials used namely the tehnik of librarian studies, namely searching, studying, understanding and analyzing various opinions, theories and concepts. The conclusion in this study is the criterion of liability in the Working Copy Act that is liability to consist of capital or shares, and individual liability that meets the criteria of micro and small businesses. The establishment of liberation libraries with the affidavit of the establishment of libraries and can be established by one person.